2007
DOI: 10.1016/j.ijpsycho.2006.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Delta and theta oscillations as risk markers in adolescent offspring of alcoholics

Abstract: Background-Visual P300 is consistently lower in alcohol dependent individuals, their offspring and subjects at risk. Delta and theta event related oscillations (ERO) are the major contributors to the P300 signal. The total and evoked power in delta and theta bands in the 300 to 700 millisecond post-stimulus window (corresponding to the zone of P3 maxima) was compared between adolescent offspring of alcoholics (high-risk) and age-matched normal controls (low-risk), to assess the utility of the risk markers.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
136
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 117 publications
(150 citation statements)
references
References 123 publications
9
136
1
Order By: Relevance
“…As expected, central and parietal theta activity for FHP subjects was lower during placebo, consistent with prior studies reporting decreased theta power in a visual P300 task (Rangaswamy et al, 2007), and during the no-go condition (Kamarajan et al, 2006) of go/no-go tasks. Low theta activity may be a marker of circuit dysfunction associated with impaired learning, memory, and selective attention (Klimesch et al, 2001;Yordanova and Kolev, 1998).…”
Section: Total Event-related Theta Activitysupporting
confidence: 90%
See 2 more Smart Citations
“…As expected, central and parietal theta activity for FHP subjects was lower during placebo, consistent with prior studies reporting decreased theta power in a visual P300 task (Rangaswamy et al, 2007), and during the no-go condition (Kamarajan et al, 2006) of go/no-go tasks. Low theta activity may be a marker of circuit dysfunction associated with impaired learning, memory, and selective attention (Klimesch et al, 2001;Yordanova and Kolev, 1998).…”
Section: Total Event-related Theta Activitysupporting
confidence: 90%
“…S-transform (Stockwell et al, 1996) is an effi cient method for extracting estimates of localized power of nonstationary evoked potentials and has been extensively used in prior alcoholism studies (Kamarajan et al, 2006;Padmanabhapillai et al, 2006;Rangaswamy et al, 2007). S-transform is a generalization of the short-time Fourier transform with a variable-length Gaussian window function sliding across time at different frequency scales.…”
Section: Event-related Oscillationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was confirmed that an increase in amplitude and power of Beta waves presents the features of electrophysiological endophenotype in the form of an increased predisposition for addiction to alcohol. It must also be said that this endophenotype is accompanied by disorders of behaviour, already in childhood, and more frequent use of psychoactive substances in adolescence, and more frequent anti-social behaviours and attitudes [48,49,50,51].…”
Section: Alcohol Initiation In Adolescence and Alcohol Addiction In Amentioning
confidence: 99%
“…Theta oscillations are reduced in alcohol-dependent individuals (Jones et al, 2006) and in the adolescent offspring of alcoholics (Rangaswamy et al, 2007), suggesting that they may be a biological marker of the predisposition to alcohol dependence.…”
mentioning
confidence: 99%